1999
DOI: 10.1109/43.811326
|View full text |Cite
|
Sign up to set email alerts
|

Voltage- and current-based fault simulation for interconnect open defects

Abstract: This paper describes a highly accurate and e cient fault simulator for interconnect opens in combinational or full-scan digital CMOS circuits. The analog behavior of the wires with interconnect opens are modeled very e ciently in the vicinity of the defect in order to predict what logic levels the fanout gates will interpret, and whether a su cient IDDQ current will be owing inside the fanout gates. The fault simulation method is based on characterizing the standard cell library with SPICE; using transistor ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…This model has been verified by measurements on manufactured designs [121,82] and by its ability to predict open defect locations [72]. The amount of charge that can be trapped on a victim net due to a full open is not well known, but Q trapped /C victim to GN D has been assumed to correspond to a variation of [−0.3V, 0.3V ] in [122] and a variation of [−1V, 1V ] in [80] and in [123] the trapped charge has been assumed negligible taking into account the possibility to eliminate this charge during IC fabrication. Due to the uncertainty of the value for the trapped charge it is not possible to fully predict the behaviour of a full open defect [124].…”
Section: Capacitive Coupling Modelmentioning
confidence: 97%
See 4 more Smart Citations
“…This model has been verified by measurements on manufactured designs [121,82] and by its ability to predict open defect locations [72]. The amount of charge that can be trapped on a victim net due to a full open is not well known, but Q trapped /C victim to GN D has been assumed to correspond to a variation of [−0.3V, 0.3V ] in [122] and a variation of [−1V, 1V ] in [80] and in [123] the trapped charge has been assumed negligible taking into account the possibility to eliminate this charge during IC fabrication. Due to the uncertainty of the value for the trapped charge it is not possible to fully predict the behaviour of a full open defect [124].…”
Section: Capacitive Coupling Modelmentioning
confidence: 97%
“…Intra-gate opens have been studied in [75,76,77,78,71,79], and it has been reported that such defects can cause delay behaviour, can increase IDDQ and can cause static faulty logic behaviour [77]. The focus in Chapter 4 is on full open defects on interconnect, since most open defects occur on interconnect [80]. The considered defect type in Chapter 4 completely separates a net from its driver ( problem" because of its similarities with a classical computer-science problem [85].…”
Section: Testing For Open Defectsmentioning
confidence: 99%
See 3 more Smart Citations